Byssus Structure and Protein Composition in the Highly Invasive Fouling Mussel Limnoperna fortunei - Li, Shiguo; Xia, Zhiqiang; Chen, Yiyong; Gao, Yangchun; Zhan, Aibin (Frontiers in Physiology, 2018)
Biofouling mediated by byssus adhesion in invasive bivalves has become a global environmental problem in aquatic ecosystems, resulting in negative ecological and economic consequences. Previous studies suggested that mechanisms responsible for byssus adhesion largely vary among bivalves, but it is poorly understood in freshwater species. Understanding of byssus structure and protein composition is the prerequisite for revealing these mechanisms. Here, we used multiple methods, including scanning electron microscope, liquid chromatography–tandem mass spectrometry, transcriptome sequencing, real-time quantitative PCR, inductively coupled plasma mass spectrometry, to investigate structure and protein composition of byssus in the highly invasive freshwater mussel Limnoperna fortunei. The results indicated that the structure characteristics of adhesive plaque, proximal and distal threads were conducive to byssus adhesion, contributing to the high biofouling capacity of this species. The 3,4-dihydroxyphenyl-α-alanine (Dopa) is a major post-transnationally modification in L. fortunei byssus. We identified 16 representative foot proteins with typical repetitive motifs and conserved domains by integrating transcriptomic and proteomic approaches. In these proteins, Lfbp-1, Lffp-2 and Lfbp-3 were specially located in foot tissue and highly expressed in the rapid byssus formation period, suggesting the involvement of these foot proteins in byssus production and adhesion. Multiple metal irons, including Ca2+, Mg2+, Zn2+, Al3+ and Fe3+, were abundant in both foot tissue and byssal thread. The heavy metals in these irons may be directly accumulated by L. fortunei from surrounding environments. Nevertheless, some metal ions (e.g. Ca2+) corresponded well with amino acid preferences of L. fortunei foot proteins, suggesting functional roles of these metal ions by interacting with foot proteins in byssus adhesion. Overall, this study provides structural and molecular bases of adhesive mechanisms of byssus in L. fortunei, and findings here are expected to develop strategies against biofouling by freshwater organisms.